MODERN VIEW OF THE ETIOPATHOGENESIS AND TREATMENT OF GUM RECESSION - Ergashevich, Sabirov Elyor; Abdujalilovich, Boymuradov Shuxrat; Khakimovna, Sultanova Rano (International Journal of Psychosocial Rehabilitation, 2020)
The reasons, conditions of development and classification of gum recessions have been described. The role of traumatic factors, important features of treatment planning and prevention have been indicated, analysis and evaluation of various treatment methods have been carried out.